Treatment methods for patients suffering from acute lymphoblastic leukemia (all) - a brief review - Zuzanna Czudy; Wojciech Pawęska; Jan Radwański; Hanna Dominik; Marika Polatowska; Anna Gadomska; Justyna Kurek; Rafał Gorzyński; Michał Garstka; Justyna Molczyk-Sieńczak (Kazimierz Wielki University, 2023)
Introduction and purpose: Acute lymphoblastic leukemia is a medical condition with underlying abnormal proliferation of cells of the lymphoid system which are blocked at an early stage of differentiation. As a result of impaired lymphocyte maturation, the proliferation and accumulation of immature blastic cells, derived from tumor-transformed bone marrow precursor cells, develop in the bone marrow. The infiltration of the bone marrow by leukemic cells results in failure of normal hematopoiesis, with subsequent anemia, thrombocytopenia and neutropenia. Acute lymphoblastic leukemia is among the most aggressive proliferative diseases, and survival time is a few to several weeks without appropriate treatment. Materials and methods: The literature available on PubMed was reviewed using the words "acute lymphoblastic leukemia ", "ALL", "acute lymphoblastic leukemia treatment". Summary: Acute lymphoblastic leukemia was managed with a chemotherapeutic drug combination for several years, with median overall survival of approximately 80% for all newly diagnosed cases. Patients with higher-risk relapses receive more intensive treatment, while patients with more favorable outcomes can avoid more toxic effects. Multicenter randomized controlled trials conducted by international collaborative efforts are helping to advance overall survival by exploring novel treatments. Hope for the future of leukemia therapy is defining the underlying molecular trails in the pathogenesis of the disease and clarifying host pharmacogenetic factors further. If successful, these efforts will allow the identification of new genes with candidate proteins for targeted therapies.